Environmental variability between the penultimate deglaciation and the mid Eemian: Insights from Tana che Urla (central Italy) speleothem trace element record. (15th November 2016) - Regattieri, Eleonora; Zanchetta, Giovanni; Drysdale, Russell N.; Isola, Ilaria; Woodhead, Jon D.; Hellstrom, John C.; Giaccio, Biagio; Greig, Alan; Baneschi, Ilaria; Dotsika, Elissavet
Abstract: A trace element record (Mg, Sr, Ba, Al, Si, P, Y, Zn) covering the ca. 133 ka to ca. 124 ka time interval was acquired from a flowstone core from Tana che Urla Cave (central Italy). It was compared with stable isotope data to investigate the environmental evolution in response to regional and extra-regional climate changes in the period corresponding to the latter part of the Penultimate Deglaciation and the first part of the Last Interglacial (Eemian). Trace element geochemical changes on centennial and millennial time scales responded to changes in hydrological input, variations in the supply and transport of catchment erosion products to the cave, including those linked to intense rainfall events, and to the state of the overlying soil and vegetation. Abrupt increases in precipitation and the progressive development of soil and vegetation occurred at ca. 132 ka, in response to the development of the global deglacial phase. The major changes in trace element composition are coherent with the previous hydrological interpretation of speleothem oxygen stable isotope composition (δ 18 O) as predominantly a rainfall-amount proxy. However, reduced growth rate persisted until ca. 130 ka, suggesting still depressed temperatures. An abrupt event of climatic deterioration, with marked decrease in precipitation and soil degradation, is apparent between ca. 131 and 130 ka. Cool-wet conditions between ca. 132 and 131 ka and the subsequent dry period may represent the local hydrological response to an interval of North Atlantic cooling and ice-rafted-debris (IRD) deposition known as Heinrich event 11 (H11). After 129.6 ka there was a rapid recovery according to all of the studied speleothem properties, indicating the onset of full interglacial conditions. A minor amplitude event of reduced precipitation is recorded within the LIG at ca. 127 ka. The record highlights the growing regional evidence for a complex penultimate deglacial climate involving major reorganization of oceanic and atmospheric patterns. Highlights: Trace element record from speleothem supports stable isotope interpretation. A coherent multiproxy framework of environmental variability. Sequence of events from the glacial-interglacial transition to the mid Eemian. Local evolution linked to extra-regional climate.